A Systematic Review and Meta-Analysis of the Differences in Mean Propulsive Velocity between Men and Women in Different Exercises - Raúl Nieto-Acevedo; Blanca Romero-Moraleda; Francisco Javier Díaz-Lara; Alfonso de la Rubia; Jaime González-García; Daniel Mon-López (Sports, 2023)
The purpose of this paper was to conduct a systematic review and meta-analysis of studies examining the differences in the mean propulsive velocities between men and women in the different exercises studied (squat, bench press, inclined bench press and military press). Quality Assessment and Validity Tool for Correlational Studies was used to assess the methodological quality of the included studies. Six studies of good and excellent methodological quality were included. Our meta-analysis compared men and women at the three most significant loads of the force–velocity profile (30, 70 and 90% of 1RM). A total of six studies were included in the systematic review, with a total sample of 249 participants (136 men and 113 women). The results of the main meta-analysis indicated that the mean propulsive velocity is lower in women than men in 30% of 1RM (ES = 1.30 ± 0.30; CI: 0.99–1.60; p < 0.001) and 70% of 1RM (ES = 0.92 ± 0.29; CI: 0.63, 1.21; p < 0.001). In contrast, for the 90% of the 1RM (ES = 0.27 ± 0.27; CI: 0.00, 0.55), we did not find significant differences (p = 0.05). Our results support the notion that prescription of the training load through the same velocity could cause women to receive different stimuli than men.